Impact of conditioning regimen intensity on the outcomes of peripheral T‐cell lymphoma, anaplastic large cell lymphoma and angioimmunoblastic T‐cell lymphoma patients undergoing allogeneic transplant. (2nd February 2022) - Savani, Malvi; Ahn, Kwang W.; Chen, Yue; Ahmed, Sairah; Cashen, Amanda F.; Shadman, Mazyar; Modi, Dipenkumar; Khimani, Farhad; Cutler, Corey S.; Zain, Jasmine; Brammer, Jonathan E.; Rezvani, Andrew R.; et al.
Summary: There have been no large studies comparing reduced‐intensity/non‐myeloablative conditioning (RIC/NMA) to myeloablative conditioning (MAC) regimens in T‐cell non‐Hodgkin lymphoma (T‐NHL) patients undergoing allogeneic transplant (allo‐HCT). A total of 803 adults with peripheral T‐cell lymphoma, anaplastic large cell lymphoma and angioimmunoblastic T‐cell lymphoma (age 18–65 years), undergoing allo‐HCT between 2008–2019 and reported to the Center for International Blood and Marrow Transplant Research with either MAC ( n  = 258) or RIC/NMA regimens ( n  = 545) were evaluated. There were no significant differences between the two cohorts in terms of patient sex, race and performance scores. Significantly more patients in the RIC/NMA cohort had peripheral blood grafts, haematopoietic cell transplantation‐specific comorbidity index (HCT‐CI) of ≥3 and chemosensitive disease compared to the MAC cohort. On multivariate analysis, overall survival (OS) was not significantly different in the RIC/NMA cohort compared to the MAC cohort (hazard ratio (HR) = 1.01, 95% confidence interval (CI) = 0.79–1.29; p = 0.95). Similarly, non‐relapse mortality (NRM) (HR = 0.85, 95% CI = 0.61–1.19; p  = 0.34), risk of progression/relapse (HR = 1.29; 95% CI = 0.98–1.70; p = 0.07) and therapy failure (HR = 1.14; 95% CI = 0.92–1.41, p  = 0.23) were not significantly different between the two cohorts. Relative to MAC, RIC/NMA was associated with a significantly lower risk of grade 3–4 acute graft‐versus‐host disease (HR = 0.67; 95% CI = 0.46–0.99, p  = 0.04). Among chemorefractory patients, there was no difference in OS, therapy failure, relapse, or NRM between RIC/NMA and MAC regimens. In conclusion, we found no association between conditioning intensity and outcomes after allo‐HCT for T‐cell NHL.